Extent of Mitochondrial Hexokinase II Dissociation During Ischemia Correlates With Mitochondrial Cytochrome c Release, Reactive Oxygen Species Production, and Infarct Size on Reperfusion. Issue 1 (31st December 2012) - Pasdois, Philippe; Parker, Joanne Elizabeth; Halestrap, Andrew Philip
Abstract : Background: The mechanisms by which ischemic preconditioning (IP) inhibits mitochondrial permeability transition pore opening and, hence, ischemia–reperfusion injury remain unclear. Here we investigate whether and how mitochondria‐bound hexokinase 2 (mtHK2) may exert part of the cardioprotective effects of IP. Methods and Results: Control and IP Langendorff‐perfused rat hearts were subject to ischemia and reperfusion with measurement of hemodynamic function and infarct size. Outer mitochondrial membrane (OMM) permeabilization after ischemia was determined by measuring rates of respiration and H2 O2 production in the presence and absence of added cytochrome c in isolated mitochondria and permeabilized fibers. IP prevented OMM permeabilization during ischemia and reduced the loss of mtHK2, but not Bcl‐xL, observed in control ischemic hearts. By contrast, treatment of permeabilized fibers with glucose‐6‐phosphate at pH 6.3 induced mtHK2 loss without OMM permeabilization. However, metabolic pretreatments of the perfused heart chosen to modulate glucose‐6‐phosphate and intracellular pHi revealed a strong inverse correlation between end‐ischemic mtHK2 content and infarct size after reperfusion. Loss of mtHK2 was also associated with reduced rates of creatine phosphate generation during the early phase of reperfusion. This could be mimicked in permeabilized fibers after mtHK2 dissociation. Conclusions: We propose that loss of mtHK2 during ischemia destabilizes mitochondrial contact sites, which, when accompanied by degradation of Bcl‐xL, induces OMM permeabilization and cytochrome c loss. This stimulates reactive oxygen species production and mitochondrial permeability transition pore opening on reperfusion, leading to infarction. Consequently, inhibition of mtHK2 loss during ischemia could be an important mechanism responsible for the cardioprotection mediated by IP and other pretreatments.